Genital herpes and human immunodeficiency virus: double trouble - Celum Connie; Levine Ruth; Weaver Marcia; Wald Anna (The World Health Organization, 2004)
The synergistic relationship between herpes simplex virus type 2 (HSV-2) and transmission of human immunodeficiency virus (HIV) can be substantial in developing countries that have high prevalences of both viral infections. Genital herpes, most frequently caused by HSV-2, has become the leading cause of genital ulcer disease worldwide. This review of recent research on genital herpes and enhanced susceptibility to, and transmission of, HIV is part of the "Advances in HIV/AIDS research series" which endeavours to form a bridge between the research into HIV and acquired immunodeficiency syndrome (AIDS) and the practice of HIV/AIDS prevention, care and support in developing countries. Research findings have shown that being seropositive for HSV-2 can increase the risk of HIV acquisition among high-risk HIV-negative people exposed to HIV and, likewise, the infectiousness of individuals co-infected with HIV-1 and HSV-2 can increase during periods of HSV-2 reactivation. These observations have led to the initiation of several intervention trials and could ultimately lead to the setting of new priorities in public health and clinical practice. WHO has recently issued new guidelines for the syndromic management of genital ulcer disease that include antiviral treatment for lesions consistent with genital herpes. The United States Centers for Disease Control and Prevention issued updated Sexually Transmitted Diseases Treatment Guidelines in 2002 that recommended the use of type-specific serological tests for diagnosing HSV-2. Recently launched proof-of-concept, HSV-2 intervention trials in several countries will help to determine the proportion of new HIV infections that could be prevented by suppression of HSV-2, and the findings from these studies will inform those involved in setting prevention and treatment priorities and strategies in developing countries.